Study of the Nanocomposite cBN/TiC-SWCNTs by Field Actived Sparck Plasma Sintering Process - Bendjemil, Badis; Mouyane, Mohamed; G. Noudem, Jacques; Bernard, Jérôme; Michel Reboul, Jean; Guel, Yannick; Houivet, David (Journal of Advances in Nanotechnology, 2020)
Cubic boron nitrid (cBN) bonded TiC and alloyed with single walled carbon nanotubes (SWCNTs or NC) ceramics matrix nanocomposites (CMNCs) tools were manufacturated by a field actived sparck plasma sintering processus (FASPS). The effects of cBN-TiC ratio, carbon nanotubes and optimisation of the sintering process on the microstructure, densification in addition mechanical and vibronic properties of NC-cBN-TiC nanocomposites were studied. The results showed that for the nanocomposite cBN-TiC vol. ratio of 8:2 with 0.1 wt% NC, it was found that microhardness incresses significantly with addition of carbon nanotubes exhibited the highest microhardness and fracture toughness. After sintering of the samples at 1800 °C, 10 mn, 75 MPa of cBN–TiC1-x, x=0.8 with and without addition of 0.1 wt% NC were characterized using field emission scanning electron microscopy (FESEM) and X-ray diffraction. The samples exhibited a dense polycrystalline structure. From the resonant Raman scattering we can locate the vibration frequency of the transformation cBN to hexagonal boron nitrid (hBN) and formation of secondary hard phase TiB2to consolid the (CMNCs) tools. The final product is hBN-TiC-TiB2-NC.The best product contained cBNx-TiC1-x (x=0.8)-0.1 wt % NC which was sintered at 1800 °C, 75 MPa for 10 mn. The Vickers hardness of cBN-TiC1-x (x=0.8) incresses with NC incorporation in the matrix The indentation fracture toughness was calculated to be 12.30 MPa m1/2 for cBNx-TiC1-x (x=0.8 -0.1 wt % NC ceramics matrix nanocomposite (CMNCs) tools with excellent wear resistant will be confirmed. The wear of cBN-TiC of the composites tools have shown that this is predominantly a chemical process involving the interaction of the tool with its environment and is restricted by the formation of protective layers on the exposed faces of the tool by the addition of carbon nanotubes (NC). The wear features of tools used in fine cutting tests under identical conditions will be compared and the results will be interpreted in terms of the existing models for the wear of cBN -based nanomaterials by the effects of the additives in the modified tools
Keywords: CMNCs; SWCNTs; FASPS; Shrinkage; Microhardness; Fracture Toughness.